Creation of Cases on the Basis of Video Materials use of Video Materials in Education - Isamuxamedova Munisxon Najmitdinovna (Research Parks Publishing LLC, 2021)
This article summarizes the importance of cases, their role in education and their positive results, as well as the use of modern technologies in today's globalized world, important aspects of working with visual aids and video tutorials.